2019
DOI: 10.1002/aoc.4821
|View full text |Cite
|
Sign up to set email alerts
|

Efficient conversion of fructose to 5‐hydroxymethylfurfural by functionalized γ‐Al2O3 beads

Abstract: Millimeter size γ‐Al2O3 beads were prepared by alginate assisted sol–gel method and grafting organic groups with propyl sulfonic acid and alkyl groups as functionalized γ‐Al2O3 bead catalysts for fructose dehydration to 5‐hydroxymethylfurfural (5‐HMF). Experiment results showed that the porous structure of γ‐Al2O3 beads was favorable to the loading and dispersion of active components, and had an obvious effect on the properties of the catalyst. The lower calcination temperature of γ‐Al2O3 beads increased the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 49 publications
1
13
0
1
Order By: Relevance
“…Besides, MCS and 10-Nb/MCS not only exhibited higher HMF yield and selectivity but also a lower humins yield than HMS and 10-Nb/HMS. This result was in accord with the previous work, which indicated the beneficial effect of catalyst hydrophobicity on the HMF formation [14]. Zhu et al [36] reported that HMF was rehydrated to 2,5-dioxo-6-hydroxyhexanal (DHH), which was thermodynamically unstable intermediate in the reaction system consisting of water and acid catalyst.…”
Section: Catalysts Screeningsupporting
confidence: 90%
See 2 more Smart Citations
“…Besides, MCS and 10-Nb/MCS not only exhibited higher HMF yield and selectivity but also a lower humins yield than HMS and 10-Nb/HMS. This result was in accord with the previous work, which indicated the beneficial effect of catalyst hydrophobicity on the HMF formation [14]. Zhu et al [36] reported that HMF was rehydrated to 2,5-dioxo-6-hydroxyhexanal (DHH), which was thermodynamically unstable intermediate in the reaction system consisting of water and acid catalyst.…”
Section: Catalysts Screeningsupporting
confidence: 90%
“…However, a low initial concentration of glucose feedstock (or a high catalyst loading level) and a substantial formation of humins limited the practical use of these catalysts. Recently, Lin et al [14] synthesized alumina (γ-Al 2 O 3 ) functionalized with alkyl groups a hydrophobic acid catalyst for HMF synthesis from fructose, while Yang et al [15] designed a series of hydrophobic silica nanoparticles for catalytic conversion of glucose into HMF. The effect of hydrophobic properties on retardation of HMF condensation to form humins was addressed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, due to its acidity, the sulfonic function catalyzed the reaction while the thiol group acted as promoter of fructose conversion. Following this study, in 2019 Lin et al [80] achieved the functionalization of alumina beads with both propyl sulfonic acid and alkyl groups. Analogously to Solis study, these materials were tested as catalysts for the production of 5-hydroxymethylfurfural.…”
Section: Sulfonic-titania Based Materialsmentioning
confidence: 98%
“…Fermentiert man Zucker, entsteht Ethanol, das sich zu Bioethylenglykol verarbeiten lässt. 8,9) Bei der Dehydrierung von Zucker entsteht 5-Hydroxymethylfurfural (HMF), 10) eine Plattformchemikalie der biobasierten Furanchemie. Die Oxidation von HMF wiederum liefert den Baustein 2,5-Furandicarbonsäure (FDCA).…”
Section: Pflanzenbasierter Kunststoffunclassified